2011
DOI: 10.1097/aln.0b013e31822a24c2
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Single Dose Systemic Dexamethasone for Postoperative Pain

Abstract: Dexamethasone at doses more than 0.1 mg/kg is an effective adjunct in multimodal strategies to reduce postoperative pain and opioid consumption after surgery. The preoperative administration of the drug produces less variation of effects on pain outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
410
2
28

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 661 publications
(474 citation statements)
references
References 56 publications
15
410
2
28
Order By: Relevance
“…This includes the beneficial effect of epidural steroid after lumbar discectomy [18] and from locally applied methylprednisolone in patients undergoing mixed lumbar surgical interventions [19]. The efficacy of glucocorticoids as part of multimodal postoperative pain treatment in different surgical procedures has recently been reviewed [20] demonstrating reductions in both pain scores and morphine consumption. Likewise, Lunn et al [21] showed that IV methylprednisolone 125 mg after total knee arthroplasty improved analgesia and promoted recovery.…”
Section: Discussionmentioning
confidence: 99%
“…This includes the beneficial effect of epidural steroid after lumbar discectomy [18] and from locally applied methylprednisolone in patients undergoing mixed lumbar surgical interventions [19]. The efficacy of glucocorticoids as part of multimodal postoperative pain treatment in different surgical procedures has recently been reviewed [20] demonstrating reductions in both pain scores and morphine consumption. Likewise, Lunn et al [21] showed that IV methylprednisolone 125 mg after total knee arthroplasty improved analgesia and promoted recovery.…”
Section: Discussionmentioning
confidence: 99%
“…All patients received perioperative dexamethasone and NSAIDs as part of multimodal analgesia and postoperative nauseavomiting prophylaxis. These are commonly used and recommended agents [1,5,6] but may have diminished the magnitude of inflammatory and pain responses in all patients due to their antiinflammatory nature [12]. All patients received aspirin as standard deep venous thrombosis prophylaxis, which again may have diminished inflammatory and pain responses in all patients.…”
Section: Discussionmentioning
confidence: 99%
“…Corticosteroids have potent antiinflammatory and antiemetic effects and have been widely used in various perioperative settings such as abdominal, cardiac, ear-nosethroat, gynecologic, and plastic surgery for reducing postoperative pain and PONV [9,19,21,22,46]. Previous studies have found that perioperative use of single, lowdose corticosteroids significantly decreased inflammatory markers after TKA [23,24,49].…”
Section: Introductionmentioning
confidence: 99%